2014
DOI: 10.1088/1367-2630/16/1/013001
|View full text |Cite
|
Sign up to set email alerts
|

Quantum breathing mode of trapped systems in one and two dimensions

Abstract: We investigate the quantum breathing mode (monopole oscillation) of trapped fermionic particles with Coulomb and dipole interaction in one and two dimensions. This collective oscillation has been shown to reveal detailed information on the many-particle state of interacting trapped systems and is thus a sensitive diagnostics for a variety of finite systems, including cold atomic and molecular gases in traps and optical lattices, electrons in metal clusters and in quantum confined semiconductor structures or na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 58 publications
(129 reference statements)
0
18
0
Order By: Relevance
“…First of all, we confirmed that the breathing mode can be accurately described with equilibrium methods. After several numerical tests with independent methods, we can draw the following conclusions [125]:…”
Section: Discussion Of the 1d Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…First of all, we confirmed that the breathing mode can be accurately described with equilibrium methods. After several numerical tests with independent methods, we can draw the following conclusions [125]:…”
Section: Discussion Of the 1d Resultsmentioning
confidence: 84%
“…While in 1D, ω rel → 2Ω, i.e. ω rel approaches its ideal quantum limit, in all considered 2D systems ω rel was found to converge to its strongly coupled classical asymptotic [125], i.e., to √ 3 Ω, for Coulomb interaction and √ 5 Ω, for dipole interaction. A physical explanation of this behavior was given from an analysis of the degree of localization of the particles which is governed by the competition of interparticle repulsion and potential (trap) energy.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations